Regeneration in White Sea sponge Leucosolenia complicata (Porifera, Calcarea). - Ereskovsky, Alexander; Lavrov, A,; Bolshakov, F,; Tokina, D (Invertebrate Zoology, 2017)
International audience Sponges (phylum Porifera) possess the remarkable regenerative abilities and great diversity of the regeneration mechanisms. The current study dealt with the regener-ation of calcareous sponge Leucosolenia complicata. Two types of experiments on L. complicata regeneration were performed: 1) the regeneration of the body wall, and 2) the regeneration of the amputated oscular tube. We have combined in vivo light microscopy and histological studies to reveal morphogenetic mechanisms and determine the cell types involved in the reparative regeneration in this sponge. The wound healing followed by complete restoration of lost body parts have been observed in both types of the experiments. The regeneration in Leucosolenia has a mode in which lost body parts are replaced by the remodeling of the remaining tissue. Epithelial morphogenesis, mainly spreading (flattening) and fusion of exo-and endopinacoderm sheets accompanied by the transdifferentiation of the choanocytes to the endopinacocytes was found to be the key morphogenetic process during regeneration in this species. The epithelial nature of the regeneration in Leucosolenia makes it similar to the regeneration in homoscleromorphs sponges and Eumetazoans.